Tác động của đa dạng hóa nguồn tài trợ tới rủi ro: Vai trò trung gian của đa dạng hóa đầu tư tài sản - Vũ Hữu, Thành; Nguyễn Minh, Hà (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
Corporate diversification is examined in terms of product diversification and in the relationship with performance or risk In this study, we put diversification into new perspectives regarding capital diversification and asset investment diversification Also, the paper indicates a mediating role of asset investment diversification in the relationship between capital diversification and risk Based on the panel data collected from listed firms in the Vietnam stock market during the period of 2008-2015 (including 470 firms with 3,760 observations), the results depict that asset diversification plays a mediating role in practical terms by employing the General Linear Structure Model (GSEM) In this role, the diversification of asset investment has contributed to an indirect effect of capital diversification on risk Additionally, the study finds an direct effect of capital diversification on risk